Simulación Desarrollada En Simulink De Un Sistema Mecanico Masa-Resorte-Amortiguador Con Fuerza Externa Variable - Rodriguez, Dr. Jorge; Romero Pabón, Julio; Romero Pabón, Cielo Esther (Revista MATUA, 2019)
This research is about the simulation of a mechanical system consisting of a mass, a spring, a shock absorber and the application of an external force, allows to understand the analytical and numerical behavior of the differential equation that governs said event. In this analysis the differential equation is obtained and solved analytically and numerically, for the numerical solution Simulink was used, since this allows the design and simulation of a system of textual and graphic form, which are fundamental elements for programming and operation of a system.